AL-HAWALAH DAN RELEVANSINYA DENGAN PEREKONOMIAN ISLAM MODERN - ., Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
The purpose of this paper is to describe al-hawalah and its relevance to modern Islamic economy. From this paper can be concluded that the application of al-Hawalah today still refer to the sources of Islamic law which allows transfer of debt payments. Some changes in placement and the addition of elements of al-Hawalah at this time because of differences of background of the development of al-Hawalah at this time with al-Hawalah at the beginning of its formation. The relevance of the concept of early al-Hawalah with modern Islamic economics lies in the functions of Islamic banks as part of the economic structure of modern Islam as channeling funds to communities whose position can be converted into Muhal Alaih as paying debts